Experimental Analysis of Twin Screw Compressor’s Energetic Efficiency Depending on Volume Ratio - Petrescu, Valentin; Savescu, Claudia; Stanescu, Teodor; Nechifor, Cristian; Niculescu, Filip; Tomescu, Sorin; Vasile, Eduard (Engineering, Technology & Applied Science Research, 2024)
The current paper presents the results of the experimental analysis to assess and optimize the twin-screw compressor’s efficiency by varying the volume ratio. The experimental tests are conducted on the compressor’s test bench, with a dedicated automation system inside the control console. The control and monitoring software allows parameter recording for subsequent visualization, data curation, and post-processing. The evaluation of screw compressor’s performance requires a simultaneous analysis of the thermodynamic and flow processes, both of which depend on the compressor’s geometry. The obtained volumetric and adiabatic efficiencies are good, with values over 0.88 and 0.69, respectively.